Education, the labour market and welfare in East Africa - Donath, Livini Tesha (2021)
This thesis consists of three empirical essays on issues relating to the analysis of the link between education and the labour market in East Africa. The first essay investigates whether returns to schooling differ according to the choice of the measure of earnings and the different periods in which workers are paid (daily, weekly, and monthly). Using comparable data from the Living Standards Measurement Study (LSMS) for Malawi, Tanzania, and Uganda, and accounting for endogeneity using Gaussian Copula and Heckman selection models, we show that pooling/aggregating earnings to different common measures produce different estimates of returns to education. Estimating separately for each pay period, the analysis also reveals that returns to education differ significantly. The analysis suggests that estimating returns separately for different periods is more reliable than pooling.